High-performance energy-efficient microprocessor design - Oklobdzija, Vojin G (Integrated Circuits and Systems, 2006)
Microprocessors of today contain close to a billion transistors, while achieving the performance of super-computers just a decade ago. Designing such processors takes hundreds of people organized into large teams. High Performance Energy Efficient Microprocessor Design is written by the world’s most prominent microprocessor design leaders from the industry and academia. It provides a complete coverage of all the aspects of a complex microprocessor design process from technology, power management, clocking, high-performance architecture, design methodologies, memory and I/O design, computer aided design, testing and design for testability. The chapters are written to provide the latest state of the art knowledge of particular aspects of microprocessor design, while including sufficient tutorial content in order to bring non-experts up to speed. High Performance Energy Efficient Microprocessor Design is intended to be a useful companion book for every design engineer working in the related areas and a source of technical information as well as a comprehensive reference in the field. It should also serve as the source book for technical and business managers involved in microprocessor based design and manufacture. The chapters are organized in a way which makes it possible to use this book as a textbook for graduate courses in advanced digital and system design. The book is intended to highlight practical problems encountered in designing state of the art processors, while yet covering fundamental principles that are independent of technology.